Inorganic dye-sensitized solar cell employing In-enriched Cu–In–S ternary colloids prepared in water media1. Issue 88 (25th September 2015) - Higashimoto, S.; Inui, S.; Nakase, T.; Azuma, M.; Yamamoto, M.; Takahashi, M.
<x xml:space="preserve">Abstract</x> Inorganic dye-sensitized solar cells employing In-enriched Cu–In–S ternary colloids prepared in water exhibit high PCE at 3.54%.